2012
DOI: 10.1021/jf300548b
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Dehydroglyasperin C through Activation of Heme Oxygenase-1 in Mouse Hippocampal Cells

Abstract: Licorice, the root of the Glycyrrhiza species ( Glycyrrhiza uralensis Fisher), is known to have antioxidant, anti-inflammatory, antiviral, and antitumor properties. The objective of this study is to explore the neuroprotective effect of dehydroglyasperin C (DGC) against glutamate-induced oxidative stress in mouse hippocampal HT22 cells. DGC significantly reduced cytotoxicity and reactive oxygen species (ROS) generation induced by glutamate in HT22 cells, whereas DGC did not restore glutathione depletion cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…DGC, DGD and ISOA all showed strong ferric reducing activities and effectively scavenged DPPH, ABTS þ and singlet oxygen radicals (Kim HJ et al 2012b). Furthermore, DGC increased the expression of haemeoxygenase-1 and MAPK phosphatase-1, suppressed the inflammation-mediated neurodegeneration, production of TNF-a, NO, ROS, NF-jB and phosphorylation of p38 MAPKs, ERK1/2, IjB-a and p65 (Kim HJ et al, 2012a;. GLD significantly inhibited NO and IL-1b release (Thiyagarajan et al 2011), attenuated colonic inflammation in mice with dextran sulphate sodiuminduced colitis (Kwon et al 2008), and decreased the iNOS mRNA expression under high-glucose levels, which indicated that GLD could be applied to diabetes-related vascular dysfunction (Yehuda et al 2015).…”
Section: Other Flavonoidsmentioning
confidence: 95%
“…DGC, DGD and ISOA all showed strong ferric reducing activities and effectively scavenged DPPH, ABTS þ and singlet oxygen radicals (Kim HJ et al 2012b). Furthermore, DGC increased the expression of haemeoxygenase-1 and MAPK phosphatase-1, suppressed the inflammation-mediated neurodegeneration, production of TNF-a, NO, ROS, NF-jB and phosphorylation of p38 MAPKs, ERK1/2, IjB-a and p65 (Kim HJ et al, 2012a;. GLD significantly inhibited NO and IL-1b release (Thiyagarajan et al 2011), attenuated colonic inflammation in mice with dextran sulphate sodiuminduced colitis (Kwon et al 2008), and decreased the iNOS mRNA expression under high-glucose levels, which indicated that GLD could be applied to diabetes-related vascular dysfunction (Yehuda et al 2015).…”
Section: Other Flavonoidsmentioning
confidence: 95%
“…Dehydroglyasperin C, as an active component of G. uralensis, can produce neuroprotective effects against glutamate-induced oxidative stress in mouse hippocampal HT22 cells by inducing heme oxygenase (HO)-1 expression; NF (erythroid-derived 2)-like 2 and the phosphoinositide-3-kinase/AKT signaling pathway may be involved in activation of HO-1 (Kim et al, 2012a). Kawakami et al (2010) reported that glycyrrhizin and 18β-glycyrrhetinic acid (10 À7 -10 À4 M) ameliorate thiamine deficiency-induced dysfunction of glutamate uptake in astrocytes and that the two compounds could inhibit protein kinase C activity.…”
Section: Effects On the Glutamatergic Systemmentioning
confidence: 99%
“…As activation of Nrf2‐mediated antioxidant enzymes could facilitate protection to epidermal cells in skin from oxidative damage (Kim et al., ; Linker et al., ; Romeo et al., ; Zhang et al., ), we hypothesized that resveratrol or resveratrol‐enriched grape peel extract could attenuate skin wrinkle formation caused by UVB‐mediated ROS production. The involvement of Nrf2 signaling pathway in resveratrol‐mediated protection of skin has been reported on cultured cells in vitro (Cao et al., ; Chan et al., ; Hirota et al., ; Liu et al., ), but to our knowledge it has never been successfully demonstrated in animal model.…”
Section: Introductionmentioning
confidence: 99%